Event-Triggered H∞ Filtering for Multiagent Systems with Markovian Switching Topologies - Jiahao Li; Tingting Zhang; Jinfeng Gao; Ping Wu (Journal of Control Science and Engineering)
This paper is concerned with the problem of event-triggered H∞ filtering for multiagent systems with Markovian switching topologies and network-induced delay. An event-triggered mechanism is given to ease the information transmission. Consider that the network topology is directed in this paper, which represents the communication links among agents. Due to the existence of network-induced delay, the time-delay approach is adopted, which can effectively deal with filtering error system. By constructing a Lyapunov-Krasovskii functional and employing linear matrix inequality technique, sufficient conditions are established to ensure the filtering error system to achieve asymptotically stable with H∞ performance index. A simulation example is given to illustrate the effectiveness of the proposed method.